Financial Literacy Among Millennials - Mohta, Anu; Shunmugasundaram, V. (International Journal of Economics and Financial Issues, 2022)
Financial literacy aids the investor in devising rational financial decisions which in turn provides financial stability to an individual and has emerged as a key to economic development in this rapidly changing financial and investing landscape. A financially illiterate person will make poor financial and investment choices which will have a detrimental effect on their financial wellbeing. The present study aims at assessing the level of basic and advanced financial literacy as well as its association with the demographic profile of millennial investors in the Delhi-NCR Region. A Chi-square test was used to analyse the data collected for the study. The findings revealed that millennials’ financial literacy is low and they have poor knowledge about the time value of the money concept and find bond prices by the interest rate concept hard to comprehend. The study concludes that financial illiteracy is acute in females. The common belief that higher education qualification is an indicator of higher financial literacy holds for the study. The millennials with a lower level of income have a lower level of basic and advanced financial literacy. These conclusions were found to be statistically significant. This paper fills the research gap of millennials’ financial literacy in India.